Vitiligo Treated by Individualized Homoeopathic Remedy: A Case Report (Homoeopathy for All, 2025)
Vitiligo is a disorder of pigmentation in which there is Focal loss of melanocytes which results in the development of patches of hypopigmentation.[1] It affects around 0.5%–1% of the world population. As high as 8.8% prevalence have been reported in India, where considerable stigma is attached to the disease.[2] It affects both sexes equally and peak incidence is between 10 and 30 yr. A positive family history is present in 20- 30% patients. Vitiligo is associated with other autoimmune disorders, e.g. thyroid disorders and alopecia areata, suggesting an autoimmune etiology.[3]
Keywords: Segmental vitiligo; Homoeopathic